Reconstruction of the Suprascapular Nerve in Brachial Plexus Birth Injury: A Comparison of Nerve Grafting and Nerve Transfers. (19th February 2020) - Manske, M. Claire; Kalish, Leslie A.; Cornwall, Roger; Peljovich, Allan E.; Bauer, Andrea S.
Abstract : Background: Shoulder external rotation recovery in brachial plexus birth injury is often limited. Nerve grafting to the suprascapular nerve and transfer of the spinal accessory nerve to the suprascapular nerve are commonly performed to restore shoulder external rotation, but the optimal surgical technique has not been clearly demonstrated. We investigated whether there was a difference between nerve grafting and nerve transfer in terms of shoulder external rotation recovery or secondary shoulder procedures. Methods: This is a multicenter, retrospective cohort study of 145 infants with brachial plexus birth injury who underwent reconstruction with nerve grafting to the suprascapular nerve (n = 59) or spinal accessory nerve to suprascapular nerve transfer (n = 86) with a minimum follow-up of 18 months (median, 25.7 months [interquartile range, 22.0, 31.2 months]). The primary outcome was the Active Movement Scale (AMS) score for shoulder external rotation at 18 to 36 months. The secondary outcome was secondary shoulder surgery. Two-sample Wilcoxon and t tests were used to analyze continuous variables, and the Fisher exact test was used to analyze categorical variables. The Kaplan-Meier method was used to estimate the cumulative risk of subsequent shoulder procedures, and the proportional hazards model was used to estimate hazard ratios (HRs). Results: The grafting and transfer groups were similar in Narakas type, preoperative AMS scores, and shoulder subluxation. The mean postoperative shoulder external rotation AMS scores were 2.70 in the grafting group and 3.21 in the transfer group, with no difference in shoulder external rotation recovery between the groups (difference, 0.51 [95% confidence interval (CI), −0.31 to 1.33]). A greater proportion of the transfer group (24%) achieved an AMS score of >5 for shoulder external rotation compared with the grafting group (5%) (odds ratio, 5.9 [95% CI, 1.3 to 27.4]). Forty percent of the transfer group underwent a secondary shoulder surgical procedure compared with 53% of the grafting group; this was a significantly lower subsequent surgery rate (HR, 0.58 [95% CI, 0.35 to 0.95]). Conclusions: Shoulder external rotation recovery in brachial plexus birth injury remains disappointing regardless of surgical technique, with a mean postoperative AMS score of 3, 17% of infants achieving an AMS score of >5, and a high frequency of secondary shoulder procedures in this study. Spinal accessory nerve to suprascapular nerve transfers were associated with a higher proportion of infants achieving functional shoulder external rotation (AMS score of >5) and fewer secondary shoulder procedures. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.